International meeting on Wolf‐Hirschhorn syndrome: Update on the nosology and new insights on the pathogenic mechanisms for seizures and growth delay. Issue 1 (25th November 2019) - Nevado, Julián; Ho, Karen S.; Zollino, Marcella; Blanco, Raquel; Cobaleda, César; Golzio, Christelle; Beaudry‐Bellefeuille, Isabelle; Berrocoso, Sarah; Limeres, Jacobo; Barrúz, Pilar; Serrano‐Martín, Candela; Cafiero, Concetta; et al.
Abstract: "An International Meeting on Wolf‐Hirschhorn Syndrome (WHS)" was held at The University Hospital La Paz in Madrid, Spain (October 13–14, 2017). One hundred and twenty‐five people, including physicians, scientists and affected families, attended the meeting. Parent and patient advocates from the Spanish Association of WHS opened the meeting with a panel discussion to set the stage regarding their hopes and expectations for therapeutic advances. In keeping with the theme on therapeutic development, the sessions followed a progression from description of the phenotype and definition of therapeutic endpoints, to definition of genomic changes. These proceedings will review the major points of discussion.